The Effects of Growth Hormone Treatment in Patients with Isolated Growth Hormone Deficiency on Hematological Parameters - Derya Şengün; Atilla Çayır (Trends in Pediatrics)
Objective: A small number of studies were reported regarding the direct and indirect effects of growth hormone (GH) and insulin-like growth factor-1 (IGF-1) especially on the erythrocyte series. The purpose of this study was to examine the effects of GH treatment (GHT) used in patients with isolated GH deficiency (IGHD) on hematological parameters.